2010
DOI: 10.1093/treephys/tpq069
|View full text |Cite
|
Sign up to set email alerts
|

Relating nutritional and physiological characteristics to growth of Pinus radiata clones planted on a range of sites in New Zealand

Abstract: Six clones of radiata pine with known differences in growth rate were examined for clonal nutritional characteristics and for physiological determinants of clonal growth rate. We compared growth, foliar characteristics and nutrient, ¹³C and ¹⁵N concentration data for the six clones in 4- to 6-year-old field trials planted over a range of nutritionally contrasting sites. These data were also compared with growth, nutrient uptake and remobilization, foliar characteristic and gas exchange data from intensive phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
7
1
1
Order By: Relevance
“…Laboratory results for the twig + leaf component indicate that the B concentration was 62 (±1.5) 68 (±2.0) and 67 (±2.8) ppm when 0, 6 and 12 g of B, respectively, were applied. These concentrations are higher than those reported for the genus (Freitas et al, 2009) and three to five times higher than those found in other forest species fertilized with B such as T. grandis (Zhou et al, 2012) and Pinus radiata D. Don (Hawkins, Xue, Bown, & Clinton, 2010). It has been observed that fertilizing Betula pendula Roth seedlings with B can improve the concentration of this nutrient in the foliage by up to 50 % (Ruuhola, Leppanen, Julkunen-Tiitto, Rantala, & Letho, 2011).…”
Section: Contenido De Nutrimentos En Las Hojasmentioning
confidence: 65%
See 1 more Smart Citation
“…Laboratory results for the twig + leaf component indicate that the B concentration was 62 (±1.5) 68 (±2.0) and 67 (±2.8) ppm when 0, 6 and 12 g of B, respectively, were applied. These concentrations are higher than those reported for the genus (Freitas et al, 2009) and three to five times higher than those found in other forest species fertilized with B such as T. grandis (Zhou et al, 2012) and Pinus radiata D. Don (Hawkins, Xue, Bown, & Clinton, 2010). It has been observed that fertilizing Betula pendula Roth seedlings with B can improve the concentration of this nutrient in the foliage by up to 50 % (Ruuhola, Leppanen, Julkunen-Tiitto, Rantala, & Letho, 2011).…”
Section: Contenido De Nutrimentos En Las Hojasmentioning
confidence: 65%
“…The high B millas indican que la concentración de B fue de 62 (±1.5), 68 (±2.0) y 67 (±2.8) ppm cuando se aplicaron 0, 6 y 12 g de B, respectivamente. Estas concentraciones son mayores que las reportadas para el género (Freitas et al, 2009) y entre tres y cinco veces más altas que las encontradas en otras especies forestales fertilizadas con B como T. grandis (Zhou et al, 2012) y Pinus radiata D. Don (Hawkins, Xue, Bown, & Clinton, 2010). Se ha observado que la fertilización con B a brinzales de Betula pendula Roth puede favorecer la concentración de dicho nutrimento en el follaje hasta en 50 % (Ruuhola, Leppanen, Julkunen-Tiitto, Rantala, & Letho, 2011).…”
Section: Contenido De Nutrimentos En Las Hojasunclassified
“…However, research on the genetic architecture of nutrient traits is sorely lacking, and nutrient traits are likely independently inherited (Beets and Jokela, 1994;Garcia et al, 1997;Xu et al, 2003), so substantial additional research would be necessary before breeding for those traits could be seriously considered. In addition, genotype x environment interaction for nutritional traits has been demonstrated for both P. radiata (Hawkins et al, 2010) and P. taeda (Tyree et al, 2009a) clones, which highlights the importance of incorporating multiple sites and treatments for making wider genetic inferences. Table 6 Mean microelement concentrations (mg/kg) in foliage, bark, stemwood, non-foliated branches (NFB) and foliated branches (FB).…”
Section: Genetic Variation In Biomass Distribution and Nutrient Traitsmentioning
confidence: 99%
“…An important question challenging biologists is the extent to which traits reflect evolutionary history (manifested as genotypic/taxonomic variation -G) and/or phenotypic responses to the environment (E) (Strand and Weisner 2004). This question has implications for agriculture and forestry (Hawkins et al 2010) and evolutionary ecology (Miner et al 2005), especially in cases where plastic responses can be shown to be adaptive. Evolutionary ecologists consider that trait plasticity is under genetic control, not independent of it (Schlichting, 1986).…”
Section: Introductionmentioning
confidence: 99%